The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18805/ijar.b-3478
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance, body condition score and carcass characteristics of Deccani lambs reared under different farming systems

Abstract: The present study was carried out to assess the effect of different farming systems on productive performance, body condition score and carcass characteristics of Deccani lambs. Thirty-six weaned lambs having 3 months of age were divided into three groups with twelve lambs in each group in under intensive (T 1 ), semi-intensive (T 2 ) and extensive (T 3 ) farming systems. The comparative mean dry matter intake (kg/day) and (kg/100kg BW) was significantly (p<0.05) higher in T 1 group when compared to other grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(12 reference statements)
3
5
1
Order By: Relevance
“…This might be due to, more quantity of DMI supplemented to intensive than semi intensive group. This result is in agree with Kochewad et al, (2018), Karaca et al, (2016), Sari et al (2014) and Aydini et al, (2017),, they reported that feed conversion was more efficient in semiintensive than intensive systems.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
“…This might be due to, more quantity of DMI supplemented to intensive than semi intensive group. This result is in agree with Kochewad et al, (2018), Karaca et al, (2016), Sari et al (2014) and Aydini et al, (2017),, they reported that feed conversion was more efficient in semiintensive than intensive systems.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
“…In general, the increased AST levels are related to liver and muscle-related diseases, and the higher ALT levels are due to the liver disorders alone. However, in the present study, these results could be attributed to the increased gluconeogenesis from protein sources, thereby stressing the liver ( Kochewad et al., 2018b ). According to Weigand et al.…”
Section: Discussioncontrasting
confidence: 60%
“…No seasonal influence was noticed for serum glucose levels; however, the sheep reared in extensive system revealed decreased serum glucose concentration. Similarly, few authors found reduced glucose concentration in sheep grazed for 8 h per day ( Kulkarni et al., 2010 ; Kochewad et al., 2018b ). The phenomenon indicates that depleted nutrition, but not the heat load, affect glucose concentration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations